Powerful rockfall incidents at Al-Hada descent and remedial measures - Sadagah, B.H.; Aazam, M.S.; Al-Amri, A.; Al-Hoseiny, O.; Al-Harbi, A. (Slope Stability 2013: Proceedings of the 2013 International Symposium on Slope Stability in Open Pit Mining and Civil Engineering, 2013)
Al-Hada descent lies at the western region of Saudi Arabia at elevation of about 2,000 m, characterised by sharp cliff. Al-Hada descent road was constructed with an elevation difference of 1,300 m between the highest and lowest heights along the road. The road alignment is intersected by eight very steep gullies of almost 45 to 80°. The gullies contain large quantities of mud, old levees and large rock blocks. Al-Hada descent road was hit by heavy rainfall lasting about two hours. The rainstorm initiated rockfalls and debris flows on steep gullies, and caused rock blocks to drop down rapidly along the gully channel. A large rock block unbalanced at high elevation, dropped from a height of about 150 m elevation difference to break three Jersey barriers and cause indents on the ascending and descending roads. This rock block continued downhill to rest on an unstable debris accumulation that received more rolling, sliding and bouncing rocks from higher steep elevations. On scrapping the debris flows at the lower elevation road segment, a number of rockfalls took place too. The temporary solution was to remove almost 230,000 m3, however unreachable debris accumulation of 65 to 80° inclination was difficult to remove and cannot be accessed. Construction of a gallery was a planned ultimate solution to protect the road from the rockfalls and debris flows. This case history outlines the analysis of rockfall and design of barriers for the Al-Hada descent road.